Synthesis of carbon microsphere-assisted snowflake-like ZnO nanomaterials for selective detection of NO2 at room temperature - Li, Qiaoyan; Cui, Yahan; Lin, Jiasheng; Zhao, Chun; Ding, Lan (Journal of industrial and engineering chemistry (Seoul, Korea), 2022)
[Display omitted] •Snowflake-like ZnO nanomaterials were prepared using carbon microspheres as sacrificial templates.•The porous structure of ZnO facilitates the diffusion and adsorption of gases.•The large specific surface area increased the chemisorbed oxygen content on the ZnO-25 surface.•The introduction of carbon microspheres improved the response of ZnO for NO2 at room temperature. In this paper, the snowflake-like ZnO nanomaterials were prepared by combining zinc salt impregnation and high-temperature calcination with carbon microspheres as the sacrificial template. The effects of ethanol concentration in aqueous solution on the microstructure and sensing properties of ZnO nanomaterials were investigated. The results showed that using 25 % ethanol-containing aqueous solution as impregnation solution, snowflake-like ZnO nanomaterials (ZnO-25) showed excellent sensing performance for NO2 at room temperature. It is mainly attributable to the rich channels and large specific surface area of the snowflake-like ZnO, which facilitates the rapid diffusion of the target gas. A large amount of chemisorbed oxygen can promote the surface reaction. In addition, the unremoved carbon during calcination promotes the electrical properties of ZnO. This strategy will provide a new sight on developing a type of sensitive NO2 gas sensing device working at room temperature.